Study of Low-Molecular Effect of Cryoprotectants on Mitochondria Respiratory Chain by Spin Probe EPR - Nardid, O. A. (Problems of Cryobiology and Cryomedicine, 2009)
Effect of low molecular cryoprotectants, glycerol, 1,2-propane diol and dimethylsulfoxide with concentrations up to 30% on activity of respiratory chain of rat liver mitochondria membranes has been studied by spin probe EPR. It has been established that lowmolecular cryoprotective substances induce inhibition of isolated organelles’ respiratory chain. It has been shown that inhibition rate of spin probe reduction and mitochondria respiration as a part of hepatocytes is lower at the same concentrations, if compared with isolated mitochondria.